Individualization, Agency and Hope: Chronicle of a summer of four women in Tromsø, Northern Norway - Loaiza Pineda, Julián David (UiT Norges arktiske universitet, 2021)
In the Covid-19 summer of 2020 in the arctic city of Tromsø, four women embarked on a research and film project about their lives. Elisa (a 28-year-old Italian woman), Sunniva (a 31- year-old Norwegian woman), Magalí (a 36-year-old Argentine woman) and Tove (an 85-year- old Norwegian woman), engaged through intimate conversations with me a researcher/filmmaker, where they exposed essential aspects of their lives, the experiences and reflections that define them. The purpose was to cover their peculiarities, looking for common that gives meaning to their daily life, partly resulting in the film "Let me hug you!" and this thesis. Through an intergenerational comparison, in these women we can observe dilemmas associated with changes in values from “classical” to “late modernity”. While values linked to the idea of responsibility are questioned, others linked to independence amplify. Depending on the social context from which they come, their self-realization is an essential factor related to simple or flexible choices, for example, love-based relations or living alone. Those are imagined worlds that, as with the real ones of their respective countries, they inhabit. Their practices and discourses are about dreams and desires, about persistent hope in and with those worlds, individually or collectively, to live the best possible life.